Σύγκριση μικροβιολογικής ποιότητας βιολογικού και συμβατικού νωπού γάλακτος - Νεοφύτου, Λούκας (Department of Agricultural Sciences, Biotechnology and Food Sciences, Cyprus University of Technology, 2013)
Up to now, studies have not shown an actual difference between organic and conventional animal products quality and safety, even though organic farming applies stricter rules concerning the farming areas, animal feeds and veterinary substances used. The aim of the present study was to compare the microbiological quality of organic and conventional milk. Samples were collected from conventional (128) and organic (10) farms. Bovine milk represented the highest amount of samples (118), followed by caprine (61), ovine (68) and mixed caprine and ovine (42). The samples were analyzed for the following parameters: (i) Total Viable Count (TVC), (ii) Enterobacteriaceae count (as a hygiene indicator), (iii) extended spectrum beta lactamase resistant colonies (ESBL) and (iv) Methicillin Resistant Staphylococcus aureus (MRSA). Results did not reveal statistically significant differences between organic and conventional bovine and ovine milk, for all parameters studied. Caprine organic milk showed significantly lower counts for TVC and ESBL, but not for Enterobacteriaceae and MRSA. Finally, mixed caprine and ovine milk showed statistically significant lower counts only for TVC. In conclusion, no significant differences were found during this study between organic and conventional milk; some low counts presented in organic milk might be attributed to good hygiene practices in the farm and during milking and not necessarily to the difference in the breeding system. The study could be repeated with a larger number of organic farms so that the result is more representative.
Keywords: Milk; Animal products